2021
DOI: 10.36877/pmmb.a0000233
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Antibiotic Susceptibility and Characterization of Vibrio parahaemolyticus Isolated from Seafood in Selangor, Malaysia

Abstract: Vibrio parahaemolyticus is one of the major foodborne pathogens owing to its cause of infectious diseases such as gastroenteritis. These diseases are often associated with the consumption of contaminated seafood. This study aims to investigate the presence of V. parahaemolyticus, their virulence, antibiotic profiles, and plasmid profiles from 77 different kinds of shellfish samples collected from wet markets and supermarkets in Selangor, Malaysia. High densities of Vibrio species ( > 5 log CFU/g) were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 128 publications
(242 reference statements)
0
27
0
Order By: Relevance
“…Reassuringly, a majority of the degrees of resistance are not high, mostly less than 10%, except for surveillance reports for environmental samples from Chhatak, Bangladesh [ 139 ], Lagos, Nigeria, Uganda [ 159 ], Eastern Cape, South Africa [ 131 ], Norway [ 83 ]; clinical samples in India [ 57 , 59 ]; seafood samples in Korea [ 134 ], Malaysia [ 27 , 32 ], Nigeria [ 121 ], and Egypt [ 75 ]. The antibiotic susceptibility pattern associated with the 16 Vibrio species covered in the existing surveillance report is highly diverse, with the carbapenem-resistance remarkably prevalent in V. parahaemolyticus [ 32 , 75 , 134 ], V. cholerae [ 59 , 140 ], V. vulnificus [ 60 ], V. fluvialis [ 57 , 131 ], V. anguillarum [ 83 ], and V. alginolyticus [ 75 ]. More worryingly, an increasing trend of intermediate-resistance transpires, indicating an evolution towards the expression of resistant phenotypes [ 140 ].…”
Section: Prevalence Of Carbapenem Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…Reassuringly, a majority of the degrees of resistance are not high, mostly less than 10%, except for surveillance reports for environmental samples from Chhatak, Bangladesh [ 139 ], Lagos, Nigeria, Uganda [ 159 ], Eastern Cape, South Africa [ 131 ], Norway [ 83 ]; clinical samples in India [ 57 , 59 ]; seafood samples in Korea [ 134 ], Malaysia [ 27 , 32 ], Nigeria [ 121 ], and Egypt [ 75 ]. The antibiotic susceptibility pattern associated with the 16 Vibrio species covered in the existing surveillance report is highly diverse, with the carbapenem-resistance remarkably prevalent in V. parahaemolyticus [ 32 , 75 , 134 ], V. cholerae [ 59 , 140 ], V. vulnificus [ 60 ], V. fluvialis [ 57 , 131 ], V. anguillarum [ 83 ], and V. alginolyticus [ 75 ]. More worryingly, an increasing trend of intermediate-resistance transpires, indicating an evolution towards the expression of resistant phenotypes [ 140 ].…”
Section: Prevalence Of Carbapenem Resistancementioning
confidence: 99%
“…Following the plasmid curing assay, the alteration from imipenem-resistant to susceptible phenotype attested to the plasmid-mediation of carbapenem resistance [ 27 ]. Plasmid profiling conducted for V. parahaemolyticus sampled from seafood in a study by Venggadasamy, Tan, Law, Ser, Letchumanan, and Pusparajah [ 32 ] revealed that 42% of the isolates harbored at least one plasmid, with the highest record at four plasmids. In contrast, 14 different plasmid patterns have been identified during the screening process.…”
Section: Mechanism To Carbapenem Resistance Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The abuse of antimicrobial agents in poultry farming is one of the main causative factors of bacterial resistance [1,2] . Likewise, irrational use of antibiotics in healthcare [3] renders antibacterial agents ineffective against bacteria such as Legionella pneumophila [4] and Mycobacterium tuberculosis [5,6] .…”
Section: Introductionmentioning
confidence: 99%